A MILP model for optimal charging coordination of storage devices and electric vehicles considering V2G technology - Carlos F., Sabillon A. [UNESP]; Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Romero, Ruben [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
In this work, a MILP formulation is proposed to solve the optimal charging coordination of electrical vehicles (EVs) and storage devices (SDs) in electrical distribution systems (EDS). EVs with vehicle-to-grid (V2G) technology are also considered. The method defines an optimal charging schedule for SDs and EVs along a day-long time period. The formulation considers the EVs arrival and departure times and their initial state of charge. The initial energy, the expected energy at the end of the time period and the allowed deep of discharge are also considered for the SDs. Additionally, the energy contribution of EVs equipped with V2G technology and distributed generation is taken into account. The presented formulation was tested in a 34-node EDS. The results show the efficiency and robustness of the methodology, and also demonstrate that the model can be used in the real-time solution of the EVs and SDs charging coordination problem in EDS.
Keywords: electric vehicles; Electrical distribution system; mixed integer linear programming; optimal charging; storage devices